Gas Holdup and Gas-Liquid Mass Transfer Investigations In an Oscillatory Baffled Column - -, Taslim; Takriff, Mohd Sobri (ASEAN Journal of Chemical Engineering, 2002)
Gas holdup and gas-liquid mass transfer were investigated in a vertical baffled column. Pure carbon dioxide (C02) was used as the dispersed phase and tap water was used as the continuous phase. Gas holdup and mass transfer rate of C02 were measured under semi-batch condition, while the liquid phase was measured in batch mode. Gas holdup was estimated as the volume fraction of the gas in the two-phase mixture in the column. Mass transfer was expressed in terms of the liquid-side volumetric mass transfer coefficient (kLa). The effects of oscillation frequency, oscillation amplitude and gas flow rate on gas holdup and mass transfer were also determined. The results showed that a significant increase in gas holdup and mass transfer could be achieved in an oscillatory baffled column compared to a bubble column. Gas holdup and mass transfer were correlated as a function of power density and superficial gas velocity.